Management of competitiveness of the banking services - Abramova, A. S.; Fedyshyn, M.F.; Marich, M.G.; Zhavoronok, A.V. (Financial and credit activity: problems of theory and practice, 2019)
In particular, the process of adapting commercial banks to rapidly changing macro- and micro-conditions is of particular importance in the context of the economic and banking sector crisis phenomena, which in turn affects the quality and, accordingly, competitiveness of banking services.Increasing the competitiveness of banking services of Ukrainian banks and ensuring the competitiveness of the domestic banking system is a prerequisite for ensuring sustainable economic growth. In view of this, the authors updated the issues of assessing the competitiveness of banking services offered in the market, using methods of economic and mathematical modeling. In assessing the competitiveness of banking services, research methods such as analysis and synthesis, the method of comparison, economic-statistical, mathematical, grouping and modeling, table and graphic are used. The work also used the modification of the Saati method as a hierarchy analysis method from the point of view of replacing the Saati estimates in the matrix of pairwise comparisons based on the numerical relations of the corresponding characteristics of the model's factors.Thus, the competitiveness of the banking service «Credit»ofJSC Oschadbank, PJSC CB «Privatbank», JSC «Raiffeisen Bank Aval», JSC «Kredobank», JSC «Alfabank»and PJSC CB «Taskombank»on the basis of its economic and consumer properties. The approach proposed by the authors to assess the competitiveness of banking and banking services, allows positioning services of a competitive bank in the financial market. For each commercial bank it is possible to determine the position and establish the competitive advantages of banking services in comparison with similar services of other commercial banks. Using the proposed model provides an opportunity to assess the competitiveness of the banking institution in terms of the competitiveness of banking services and should become a complete and informative information tool for managing the competitive advantages of domestic commercial banks.
Keywords: banking system, competitiveness, commercial bank, banking market, credit, Saati method, modeling.